Feasibility and accuracy of variant PCR assays for low- and middle-income countries in SARS-CoV-2 surveillance. (March 2022) - Jayadas, T.T. Pramanayagam; Jeewandara, C.; Jayathilaka, D.; Ranasinghe, D.; Ariyarathne, D.; Wijesinghe, A.; Gunasinghe, D.; Gomes, L.; Madushanka, D.; Dissanayake, O.; Harvie, M.; Bary, F.; et al.
Abstract : Purpose: Surveillance of different SARS-CoV-2 variants of concern (VOCs) is a crucial aspect in control of the pandemic. Although sequencing is the gold-standard to detect VOCs, it is labor intensive and is costly. We compared a cost-effective real-time PCR assay that detects single nucleotide polymorphisms (SNPs) of VOCs, with next generation sequencing (NGS) in surveillance of VOCs. Methods & Materials: A total of 782 SARS CoV-2 PCR positive samples From May – August 2021 were screened using two variant RT-qPCR assays (Seegene Allplex™ SARS-CoV-2 Variant Assay I and II), which detects 7 SNPs in the spike protein assigning them to one of the VOCs. We compared the results of the variant RT-qPCR with Illumina (n=97) and Oxford Nanopore (n=53) platforms in a subset of samples (n=150). Sequences with > 25x coverage were used and assigned to a Pangolin lineage. Results: 516 samples amplified for N501Y and HV69/70 deletion of the spike protein were assigned as alpha (B.1.1.7). Two samples with spike K417N mutation along with N501Y and E484K were considered to be beta (B.1.351) and 175 samples which are only positive for spike L452R mutation were considered to be delta (B.1.617). 120/156 samples designated as alpha, 22/175 designated as delta and 2 samples designated as beta by RT-qPCR were sequenced either by Illumina or Oxford nanopore platforms. The sequencing results showed a 100% accuracy with the variant RT-qPCR for identification of VOCs. Conclusion: RT-qPCR that detected SNPs specific for VOCs, appear to be highly sensitive and specific in detection of VOCs and had a similar specificity of genomic sequencing. Therefore, this could be a rapid and less expensive method for surveillance of VOCs, in lower income countries. However, as it only detects specific SNPs, any emerging mutations of concern in these VOCs or newly emerging variants, will not be detected.